Proceedings of the Second International Conference on Human-Agent Interaction 2014
DOI: 10.1145/2658861.2658882
|View full text |Cite
|
Sign up to set email alerts
|

Daily support robots that move on the body

Abstract: Today, wearable devices such as Google Glass [1] and SmartWatch[2] are gathering attention. These devices can constantly support us by being worn on a daily basis. In contrast, although we can also find an increase of personal robots in daily life, "wearable robots" are not so prevalent.We focus on wearable robots and the "fixed" points on which they are worn. We believe that they can provide more continuous and suitable support in a variety of ways by moving automatically on our bodies. Therefore, we propose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Some of these studies focus on moving on clothing, such as the cm-scale companion robot developed by Liu and Wu et al [18], [19], [20], [21], where they demonstrated autonomous navigation on flexible materials. Saga et al [22] also proposed a small wearable companion robot that can move on a dedicated belt with fixed rails. Another robot that can move on clothing was proposed by Dementyev et al [23], which is smaller and lighter than previous examples (40 × 26 × 26 (mm), 20 g).…”
Section: A Miniature Robots That Move On the Bodymentioning
confidence: 99%
“…Some of these studies focus on moving on clothing, such as the cm-scale companion robot developed by Liu and Wu et al [18], [19], [20], [21], where they demonstrated autonomous navigation on flexible materials. Saga et al [22] also proposed a small wearable companion robot that can move on a dedicated belt with fixed rails. Another robot that can move on clothing was proposed by Dementyev et al [23], which is smaller and lighter than previous examples (40 × 26 × 26 (mm), 20 g).…”
Section: A Miniature Robots That Move On the Bodymentioning
confidence: 99%
“…The concept of Parasitic Mobility [13] illustrates sensor nodes that can jump from one human host to another. Perhaps, the most closely related work developed a mouse-like robot that moves on a rail mounted on the arm [23]. In this early work, authors do a limited user study to explore how the participants feel about the robot.…”
Section: Actuation In Human-computer Interactionmentioning
confidence: 99%